Organically pillared layer framework of [Eu(NH2-BDC)(ox)(H3O)] - Supaphorn Thammakan (2020)
© Acta Cryst. 2019. The non-porous three-dimensional structure of poly[(μ5-2-aminobenzene-1,4-dicarboxylato)(μ6-oxalato)(oxomium)europium(III)], [Eu(C8H5NO4)(C2O4)(H3O)] n or [EuIII(NH2-BDC)(ox)(H3O)] n (NH2-BDC2- = 2-aminoterephthalate and ox2- = oxalate) is constructed from two-dimensional layers of EuIII-carboxylate-oxalate, which are connected by NH2-BDC2- pillars. The basic structural unit of the layer is an edge-sharing dimer of TPRS-EuIIIO9, which is assembled through the ox2- moiety. The intralayer void is partially occupied by TPR-EuIIIO6 motifs. Weak C - H⋯O and strong, classical intramolecular N - H⋯O and intermolecular O - H⋯O hydrogen-bonding interactions, as well as weak π-π stacking interactions, affix the organic pillars within the framework. The two-dimensional layer can be simplified to a uninodal 4-connected sql/Shubnikov tetragonal plane net with point symbol {44.62}.